Penguatan Manajemen Usaha Krupuk Gandum Di Desa Kediri Selatan Lombok Barat - Ida Ayu Nursanty; Baehaqi Syakbani; Rusli Amrul; Fariantin, Erviva; I Nengah Arsana; I Made Murjana; M. Wahyullah; Nendy Pratama Agusfianto; Elvina Setiawati; Yusi Faizathul Octavia (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
Strengthening business management in the wheat cracker business group in South Kediri Village, West Lombok is an implementation of community service carried out by STIE AMM Mataram lecturers. Strengthening business management is in order to increase the group's understanding of the problems that arise in carrying out the wheat cracker business. The problems that arise during mentoring are that business development does not have a clear plan so that the goals and objectives of the wheat cracker business to be achieved are not clear, there is no effective marketing promotion and there is a lack of access to collaborate with other parties. The method of implementing this service uses discussion and assistance in making product labeling and making banners as well as introducing promotions through the South Kediri Village website. The results obtained from this service are that the group understands business management, the group understands marketing using labeling and digitalization promotion through the South Kediri Village website.